2018
DOI: 10.1242/dev.169664
|View full text |Cite
|
Sign up to set email alerts
|

A cargo model of yolk syncytial nuclear migration during zebrafish epiboly

Abstract: In teleost fish, the multinucleate yolk syncytial layer functions as an extra-embryonic signaling center to pattern mesendoderm, coordinate morphogenesis and supply nutrients to the embryo. External yolk syncytial nuclei (e-YSN) undergo microtubule-dependent movements that distribute the nuclei over the large yolk mass. How e-YSN migration proceeds, and the role of the yolk microtubules, is not understood, but it is proposed that e-YSN are pulled vegetally as the microtubule network shortens from the vegetal p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 78 publications
1
5
0
Order By: Relevance
“…Thus, disruption of microtubule networks in the yolk cell of MZsyne2b mutants may also contribute to impaired YSN movements during epiboly. This observation is consistent with a previous report showing that overexpression of the dominant negative Syne2a KASH slows migration speeds of YSN (Fei et al, 2019). Thus, our results further illustrate an important role of the LINC complex in coordinating nuclear movements.…”
Section: Discussionsupporting
confidence: 93%
“…Thus, disruption of microtubule networks in the yolk cell of MZsyne2b mutants may also contribute to impaired YSN movements during epiboly. This observation is consistent with a previous report showing that overexpression of the dominant negative Syne2a KASH slows migration speeds of YSN (Fei et al, 2019). Thus, our results further illustrate an important role of the LINC complex in coordinating nuclear movements.…”
Section: Discussionsupporting
confidence: 93%
“…Between dome and 50% epiboly, when the EVL is most proliferative, Venus-Rab25a and eGFP-Rab25b appeared to localize near centrosomes during mitosis and then moved towards the opposing poles of dividing cells (Figure 1B, arrowheads; Video 1). Injection of mcherry-rab25b mRNA into transgenic animals expressing Tubulin-GFP (Fei et al, 2019) confirmed that mCherry-Rab25b localized near centrosomes and dissipated following cell division (Figure 1C; arrows). During cytokinetic abscission, co-expression of eGFP-Rab25b with the midbody marker mCherry-Mklp1 demonstrated that eGFP-Rab25b dynamically localized within intercellular bridges adjacent to the midbody (Figure 1D), the sites of bridge scission.…”
Section: Resultsmentioning
confidence: 69%
“…Venus-Rab25a and eGFP-Rab25b appeared to localize near centrosomes during mitosis and then moved towards the opposing poles of dividing cells (Figure 1B; arrowheads; Video S1). Injection of mcherry-rab25b mRNA into transgenic animals expressing Tubulin-GFP (Fei et al, 2019) confirmed that mCherry-Rab25b localized near centrosomes and dissipated following cell division ( Figure 1C; arrows). Recycling endosomes (REs) become positioned near centrosomes during mitosis, suggesting that Rab25 associates with REs in the EVL, as in other systems (Casanova et al, 1999;Hehnly and Doxsey, 2014).…”
Section: Fluorescently Tagged Rab25 Localizes Near the Plasma Membranmentioning
confidence: 69%